2023
DOI: 10.1093/mnras/stad328
|View full text |Cite
|
Sign up to set email alerts
|

V994 Herculis: a unique triply eclipsing sextuple star system

Abstract: We report the discovery with TESS of a third set of eclipses from V994 Herculis (TIC 424508303), previously only known as a doubly-eclipsing system. The key implication of this discovery and our analyses is that V994 Her is the second fully-characterized (2+2) + 2 sextuple system, in which all three binaries eclipse. In this work, we use a combination of ground-based observations and TESS data to analyze the eclipses of binaries A and B in order to update the parameters of the inner quadruple’s orbit (with a d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The authors also reported updated masses of 3.01 ± 0.06 M ⊙ , 2.58 ± 0.05 M ⊙ , 1.84 ± 0.03 M ⊙ , and 1.93 ± 0.04 M ⊙ for the Aa, Ab, Ba, and Bb components, respectively. Ultimately, Zasche et al (2023) reported the discovery of a third set of eclipses in the TESS space-based and archival ground-based photometric data, which makes the system a triply eclipsing sextuple star system. The authors refined the orbital period of the A(Aa+Ab)-B(Ba+Bb) core system to 1062 ± 2 days and reported on its close to 3:2 mean motion resonance.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also reported updated masses of 3.01 ± 0.06 M ⊙ , 2.58 ± 0.05 M ⊙ , 1.84 ± 0.03 M ⊙ , and 1.93 ± 0.04 M ⊙ for the Aa, Ab, Ba, and Bb components, respectively. Ultimately, Zasche et al (2023) reported the discovery of a third set of eclipses in the TESS space-based and archival ground-based photometric data, which makes the system a triply eclipsing sextuple star system. The authors refined the orbital period of the A(Aa+Ab)-B(Ba+Bb) core system to 1062 ± 2 days and reported on its close to 3:2 mean motion resonance.…”
Section: Discussionmentioning
confidence: 99%
“…More recently Zasche et al (2021) present an extensive sample of 162 early-type binary systems showing apsidal motion located in the Large Magellanic Cloud. This point is particularly important given that light curves and apsidal motion modelling were carried out for the first time for several systems simultaneously and in an environment with a chemical composition different from solar (for a more recent reference on apsidal motion measurements, see Zasche et al 2023).…”
Section: Introductionmentioning
confidence: 99%